Investigation on the wear properties of primary Si modified Al-20Si alloy - Raju K.; Sherwin C.; Ojha S.N. (My University, 2025)
In the present study, Al-20Si alloy has been modified by Cu-13P master alloy to obtain Al-20Si-0.1P alloy. The wear properties of Al-20Si-0.1P alloy have been investigated and compared with that of Al-20Si alloy. The microstructure of Al-20Si-0.1P alloy consisted of primary and eutectic silicon distributed in the Al matrix. The size of primary Si is much smaller than that observed in Al-20Si alloy. Wear tests have been conducted over a wide range of loads and sliding velocities. It has been observed that the wear rates of Al-20Si-0.1P alloy are lower than that of Al-20Si alloy. The coefficient of friction is more or less constant in both the alloys but is low in Al-20Si-0.1P alloy. The better wear resistance of Al-20Si-0.1P alloy is discussed in the light of its modified microstructure evolved during solidification.